2005
DOI: 10.1055/s-2005-865224
|View full text |Cite
|
Sign up to set email alerts
|

Stereo- and Regioselective Zinc-Mediated Ring-Opening of Epoxides with Diselenides

Abstract: Two convenient rapid, efficient, stereoselective and highly regioselective methods for the synthesis of b-hydroxy selenides by the direct opening of epoxides with diselenides in acetonitrile in the presence of either Zn/AlCl 3 or zinc powder in aqueous sodium hydroxide solution are described. These methods appear to be competitive with the other methods previously reported.b-Hydroxy selenides are valuable selenium intermediates in organic synthesis; 1 they can be converted to allylic alcohols, olefins, bromohy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 12 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…In situ reaction of the so generated zinc selenolates with epoxides afforded β-hydroxy selenides in high yields with good regioselectivity. 14 Santi, Tiecco and co-workers reported an efficient zinc-mediated reduction of diselenides into the corresponding selenols, occurring in a biphasic system under acidic conditions (Scheme 4). 15 Selenols generated under these conditions react in situ with epoxides, enabling the synthesis of β-hydroxy selenides.…”
Section: Synthesis Of Unsymmetric Selenides and Telluridesmentioning
confidence: 99%
“…In situ reaction of the so generated zinc selenolates with epoxides afforded β-hydroxy selenides in high yields with good regioselectivity. 14 Santi, Tiecco and co-workers reported an efficient zinc-mediated reduction of diselenides into the corresponding selenols, occurring in a biphasic system under acidic conditions (Scheme 4). 15 Selenols generated under these conditions react in situ with epoxides, enabling the synthesis of β-hydroxy selenides.…”
Section: Synthesis Of Unsymmetric Selenides and Telluridesmentioning
confidence: 99%
“…Using selenolate anions, the S N 2 ring opening of epoxides is another common method for access to β ‐hydroxy selenides. The selenolate anions can be generated by the treatment of diphenyl diselenide with Na, Zn, NaBH 4 , zinc/aluminum (III) chloride, tributylphosphine in an alkaline medium and sodium hydroxymethanesulfinate . They are also transformed from benzeneselenol under supramolecular catalysis in the presence of β ‐cyclodextrin and promoted by [Bmim]BF 4 .…”
Section: Introductionmentioning
confidence: 99%
“…These promoting agents include Sm-TMSCl, 8 ytterbium(III) chalcogenolate complexes, 9 NaBH 4 /NaOH under microwave irradiation, 10 tetrathiomolybdate, 11 indium compounds, 12,13 PBu 3 , 14,15 and zinc compounds. 16,17 Recently, Chen and co-worker reported that Rongalite ® -promoted highly regioselective synthesis of β-hydroxyselenides by grinding under solvent-free conditions, 18 which could not be applied to large-scale synthetic procedures with a glass pestle in the glass mortar using manual labour. Also, when treated with a base Rongalite ® readily decomposes into the toxic formaldehyde.…”
mentioning
confidence: 99%